Constitutional Dynamics of Employment Copyright Law in a Legal Sociology Perspective - Ashady, Suheflihusnaini; Dudy, Aryadi Almau (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The Constitutional Court on November 25 2021 in its decision stated that Law Number 11 of 2020 concerning Job Creation must be declared conditionally unconstitutional. The government then made improvements through Government Regulation Number 2 of 2022 concerning Job Creation which was then promulgated with Law No. 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law. In principle, the existence of law is to create order and order in society, this is in direct contrast to the process of drafting the Job Creation Law which was filled with various criticisms and efforts to prevent the a quo Law from being passed by the Government and the House of Representatives. Sociology of Law views that society must have access to justice. Law refers to a rule of life that is in accordance with the ideals of living together, namely justice. An order in which only the public interest takes priority, namely the participation of everyone in the idea of justice will be achieved perfectly.